Extraction and Characterization of Gelatin from Mackerel (Scomber scombrus) and Sea bass (Dicentrarchus labrax) Bones - Yasemen Yanar; Mehmet Gökçin (Turkish Journal of Agriculture: Food Science and Technology)
The aims of this study were to determine the physicochemical properties of extracted gelatins from mackerel (Scomber scombrus) and sea bass (Dicentrarchus labrax) bones and compare with those of commercial fish and bovine gelatins. The yield of gelatin obtained from the bone of mackerel and sea bass were 5.98 and 6.20%, respectively. Two extracted gelatins showed higher protein content, lower moisture content compared to both commercial gelatins, indicates that the gelatin has considerably high purity. Melting temperatures of mackerel and sea bass bone gelatins were 25.5 and 23°C, respectively. Mackerel bone gelatin was yellow in appearance and higher L* value than both commercial gelatins. It can be concluded from the present study that mackerel and sea bass bone are a prospective source to produce gelatin in good yield with desirable functional properties comparable to commercially available mammalian and fish gelatins.